Factores de riesgo cardiovascular en estudiantes de la Universidad Austral de Chile - Martínez S,María Adela (Sociedad Médica de Santiago, 2012)
Background: Cardiovascular diseases are related to particular lifestyle patterns and the presence of cardiovascular risk factors (CVRF). Aim: To evaluate the presence of CVRF in students from Universidad Austral de Chile (UACh). Material and Methods: CVRF were evaluated in 385 university students aged 17 to 26years (63% women). Personal background, lifestyle, anthropometry, blood pressure, serum lipids and blood glucose were evaluated. Results: Eighty eight percent of evaluated students had sedentary habits, 19% had high LDL cholesterol levels, 40% had high blood pressure, 28% smoked, 29% were overweight or obese and 20% had some stress level. Conclusions: There is a high frequency of non-healthy lifestyles and cardiovascular risk factors in this sample of university students.